The Evaluation of Student Fitness Levels in Exercise Science and Physical Education Teacher Education Programs. Issue 1 (2nd January 2019) - Blackshear, Tara B.; Barton, Andrea T.; Moxley, Jennifer
ABSTRACT: The debate on whether kinesiology students should undergo fitness testing is controversial. Some are strong proponents of fitness testing, while others are in strong opposition. As advocates for fitness testing among kinesiology majors, we aimed to assess the fitness levels of Exercise Science and Physical Education Teacher Education majors and evaluate current physical education teacher education (PETE) fitness criterion. One hundred and sixteen participants (males N  = 49; females N  = 67) underwent health-related fitness assessments. 37% of males and 51% of females met PETE's fitness criteria. Both groups performed significantly better in body fat percentage and upper body strength than PETE's acceptable (average) standards; however, most were significantly lower than target (above average) standards. Presented are fitness passing criteria for PETE majors and fitness reporting that aids in improved fitness tracking and accountability. We also highlight the need for NASPE and SHAPE America to clearly define fitness expectations for PETE majors and encourage other kinesiology faculty to consider implementing fitness testing in their programs.